Enpp1 is an anti-aging factor that regulates Klotho under phosphate overload conditions - Watanabe, Ryuichi (Sci Rep, 2017)
Control of phosphate metabolism is crucial to regulate aging in mammals. Klotho is a well-known anti-aging factor that regulates phosphate metabolism: mice mutant or deficient in Klotho exhibit phenotypes resembling human aging. Here we show that ectonucleotide pyrophosphatase/phosphodiesterase 1 (Enpp1) is required for Klotho expression under phosphate overload conditions. Loss-of-function Enpp1 (ttw/ttw) mice under phosphate overload conditions exhibited phenotypes resembling human aging and Klotho mutants, such as short life span, arteriosclerosis and osteoporosis, with elevated serum 1,25(OH)(2)D(3) levels. Enpp1 (ttw/ttw) mice also exhibited significantly reduced renal Klotho expression under phosphate overload conditions, and aging phenotypes in these mice were rescued by Klotho overexpression, a low vitamin D diet or vitamin D receptor knockout. These findings indicate that Enpp1 plays a crucial role in regulating aging via Klotho expression under phosphate overload conditions.